Contributions of mosques towards building Malay society: a case study on Masjid Wilayah Persekutuan, Kuala Lumpur - Afridi, Muhammad Adil Khan (2011)
Malaysia is a country which is known for the heavy Islamic moral values presence in its culture and traditions. Mosques in Malaysia are well known for their beauty and captivating architecture. At the same time, the history of Islamic civilization is closely linked to the mosque, as it is the main centre for spreading the Islamic culture and knowledge everywhere in the world. This is my pleasure to write a paper on “Contributions of Mosques towards Building Malay Society: a case study on Masjid Wilayah Persekutuan, Kuala Lumpur”, which is not only the land mark of Kuala Lumpur, but it is also a structural marvel that become a pride of the Islamic world with its beautiful and unique architectural features. While I was writing this paper, I met so many officials of this beautiful Mosque. Officials of the Masjid Wilayah are so helpful and informative as it helped me a lot to collect the information’s about the mosque, some of are namely; Ustaz Zakariah Isa, chief Imam of Masjid Wilayah, Ustaz Abdul Haleem Zakaria, Imam of Masjid Wilayah, Brother Uthman Mustafa, Director of Jakim, Brother Dato Che Mat, Chairman of Jawi, Ustazah Umme Kulsoom Principal of Masjid Wilayah School, Ustazah Fathiyyah binti A.Rahman, Senior Assistant Director. I surprised when I was informed from the officials that, this mosque is not only a Mosque but a complete world of services and facilities under the name of Masjid Wilayah Persekutuan, which is busy day and night in building the Malay society. Some facilities are: 1.Friday congregations, 2. Morning speech, Zohor speech, 3. Qur’an class, 4. Fiqh class, 5.Arabic class, 6. Qiyam-ul-Lail, 7. Hospital’s visit program, 8. Program for single mother, 9.Complete school program, 10. Nursery program, 11. School holidays program for youth, 12.Basic religious teaching program, 13. Health program, 14. Cooking class, 15. Flower making class, 16.Aerobic class (fitness class), 17. Blood donation program, 18. Iftar program and Sohur program, 19. Eid-ul-Adha cow slaughtering program, 20. Friday Bazar, 21.Funeral preparation program. With this note, I would like to thank from my heart to the organizers of the International conference on Islamic Civilization and Malay Identity 2011(ICICMI 2011) who allowed me to present this paper. I hope this study will be an informative reference for the people who want to know about services of Masjid Wilayah and its features.